Publishing SNP Genotypes of Human Embryonic Stem Cell Lines: Policy Statement of the International Stem Cell Forum Ethics Working Party - Knoppers, Bartha M. (Humana Press Inc, 2011)
Novel methods and associated tools permitting individual identification in publicly accessible SNP databases have become a debatable issue. There is growing concern that current technical and ethical safeguards to protect the identities of donors could be insufficient. In the context of human embryonic stem cell research, there are no studies focusing on the probability that an hESC line donor could be identified by analyzing published SNP profiles and associated genotypic and phenotypic information. We present the International Stem Cell Forum (ISCF) Ethics Working Party’s Policy Statement on “Publishing SNP Genotypes of Human Embryonic Stem Cell Lines (hESC)”. The Statement prospectively addresses issues surrounding the publication of genotypic data and associated annotations of hESC lines in open access databases. It proposes a balanced approach between the goals of open science and data sharing with the respect for fundamental bioethical principles (autonomy, privacy, beneficence, justice and research merit and integrity).